Zola Award Winner: "I Ain't Had Much Schooling": The Ritual of the Examination and the Social Construction of Impairment - Rembis, Michael (Disability Studies Quarterly, 2008)
In this article, Rembis uses case files and other records from the state training school for girls in Geneva, Illinois, as well as published studies of female juvenile delinquents, to analyze the psychological evaluation of inmates from the perspective of both female experts and their female subjects. Throughout the first half of the twentieth century, experts conducting research at Geneva consistently argued that an overwhelmingly high percentage of its inmates were "feebleminded" or "mentally defective." Analyzing the testing that occurred at Geneva reveals not only the importance of eugenics and other psy discourses in the construction of mental "defect," but also the contestation, negotiation, and redefinition that undergirded the formation of historically contingent definitions of impairment. Many disability theorists and activists have viewed impairment as a prediscursive state of being, as politically neutral, given, natural, and timeless. As this article shows impairment is not ahistorical. It too has a history, a genealogy. The ritual of modern psychological examination was a critical new modality of power that greatly affected the lives of its subjects; the examiner observed, measured, recorded, defined, and treated, all through a process in which power relations between scientist and subject were far from equal, but the ritual of the exam did afford its subjects some room for negotiation and redefinition. Young women incarcerated at Geneva actively participated in the examination and in the formation of their own individuality, and in some cases affected not only their own lived experience, but also dominant perceptions of "mental defect" and eugenic commitment.